Corrosion-resistant flame-retardant powder coating and preparation method thereof

By using a specific composition powder coating, using the composite of modified nanoalumina and nanocalcium silicate and the silane coupling agent, the shortcomings of existing powder coatings in terms of corrosion resistance and flame retardancy are solved, and good performance in extreme environments is achieved, while avoiding cost increase and environmental pollution.

CN119875470APending Publication Date: 2025-04-25廊坊市亚龙三惠科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510151183.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing powder coatings have shortcomings in corrosion resistance and flame retardancy, especially in extreme environments, and existing methods increase coating costs and may cause environmental pollution.

Method used

Powder coatings consisting of epoxy resin, polyimide resin, modified nanoalumina, nanocalcium silicate, graphene nanosheets, expanded graphite, polyamide curing agent, silane coupling agent, leveling agent, dispersing agent, antioxidant and imidazole-based accelerator are used to improve the corrosion resistance and flame retardancy of the coating by modifying the combination of nanoalumina and nanocalcium silicate and the silane coupling agent.

Benefits of technology

It significantly improves the corrosion resistance and flame retardancy of the coating, and can maintain good performance in extreme environments, avoiding the defects of increasing costs and polluting the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and provides a corrosion-resistant flame-retardant powder coating and a preparation method thereof. The corrosion-resistant flame-retardant powder coating is prepared from the following raw materials in parts by weight: 45 to 55 parts of epoxy resin, 15 to 25 parts of polyimide resin, 10 to 12 parts of modified nano aluminum oxide, 6 to 8 parts of nano calcium silicate, 2 to 3 parts of graphene nanosheets, 8 to 10 parts of expanded graphite, 18 to 22 parts of polyamide curing agent, 2 to 4 parts of silane coupling agent, 1 to 1.4 parts of flatting agent and 0.5 to 1.5 parts of dispersing agent. 0.5 to 0.7 part of an antioxidant; and 0.5 to 1.5 parts of an imidazole accelerant. The core of the invention lies in that the corrosion resistance and flame retardancy of the coating are remarkably improved through accurate proportioning and a preparation process; meanwhile, the preparation method is simple in process, low in cost and environment-friendly, and large-scale production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a corrosion-resistant flame-retardant powder coating and a preparation method thereof. Background Art

[0002] With the development of modern industry, the requirements for coating performance are increasing, especially in terms of corrosion resistance and flame retardancy. As a highly efficient, environmentally friendly and low-cost coating form, powder coating has been widely used in many fields due to its unique advantages. In the chemical, shipbuilding, bridge, construction and other industries, coatings not only need to have basic decorative and protective functions, but also need to have excellent corrosion resistance and flame retardancy. For example, in the chemical industry, equipment is often exposed to corrosive media. If the corrosion resistance of the coating is insufficient, it will seriously affect the life and safety of the equipment. In the shipbuilding and bridge industries, coatings need to have fireproof properties to prevent fire accidents.

[0003] However, existing powder coatings still have shortcomings in terms of corrosion resistance and flame retardancy. Although some coatings have certain corrosion resistance, they perform poorly in flame retardancy; while other coatings have good flame retardancy but lack corrosion resistance.

[0004] At present, although some methods for preparing corrosion-resistant and flame-retardant powder coatings have been proposed, these methods still have some shortcomings. For example, some methods improve the corrosion resistance and flame retardancy of coatings by adding a large amount of flame retardants and preservatives, but this will increase the cost of coatings and may cause environmental pollution; others have certain corrosion resistance and flame retardancy, but their performance is still insufficient in some extreme environments.

[0005] In view of the above problems, the present invention provides a corrosion-resistant flame-retardant powder coating and a preparation method thereof. Summary of the invention

[0006] The invention provides a corrosion-resistant flame-retardant powder coating and a preparation method thereof, which improves the corrosion resistance and flame retardancy of the coating and can still maintain a certain corrosion resistance under extreme environments.

[0007] The technical solution of the present invention is as follows: In the first aspect, the present invention provides a corrosion-resistant flame-retardant powder coating, which is composed of the following raw materials in parts by weight: 45-55 parts of epoxy resin, 15-25 parts of polyimide resin, 10-12 parts of modified nano-alumina, 6-8 parts of nano-calcium silicate, 2-3 parts of graphene nanosheets, 8-10 parts of expanded graphite, 18-22 parts of polyamide curing agent, 2-4 parts of silane coupling agent, 1-1.4 parts of leveling agent, 0.5-1.5 parts of dispersant, 0.5-0.7 parts of antioxidant and 0.5-1.5 parts of imidazole accelerator.

[0008] As a further technical solution, the epoxy resin has a molecular weight of 400-500 and an epoxy equivalent of 210-240 g / eq; the polyimide resin has a viscosity of 30000-60000 mPa·s at 50° C. and a resin solid content of 80 wt%-85 wt%.

[0009] As a further technical solution, the preparation method of the modified nano-alumina includes: adding nano-alumina to deionized water for ultrasonic dispersion, then adding ZnCl2·6H2O, continuing ultrasonic dispersion to obtain a mixed solution, adding ammonia water with a concentration of 1 mol / L under stirring conditions until the pH is 10, continuing stirring, and then adding deionized water until the pH is 7, filtering and drying to obtain the product.

[0010] As a further technical solution, the weight ratio of the nano-alumina to ZnCl2·6H2O is 1:3-5.

[0011] As a further technical solution, the power of the ultrasonic dispersion is 100-120W; the rotation speed of the stirring is 120-140r / min.

[0012] As a further technical solution, the dropping speed of the ammonia water is 9-11 mL / min.

[0013] As a further technical solution, the model of the silane coupling agent is any one of KH550, KH560 and KH570; the polyamide curing agent includes polyamide curing agent 650 or polyamide curing agent 651; and the imidazole accelerator includes imidazole accelerator 2MZ-A or imidazole accelerator 1B2PZ.

[0014] As a further technical solution, the model of the leveling agent is BYK-310; the dispersant is dispersant 5040; and the antioxidant is antioxidant 168.

[0015] In a second aspect, the present invention provides a method for preparing a corrosion-resistant flame-retardant powder coating, the steps comprising: S1. Drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at a temperature of 55-65° C. for 100-120 min; S2, mixing the epoxy resin and the polyimide resin with the powder dried in step S1, maintaining the rotation speed at 160-200rpm and stirring for 20-30min, then sequentially adding silane coupling agent, leveling agent, dispersant and antioxidant and continuing stirring for 20-30min, finally adding polyamide curing agent and imidazole accelerator, continuing stirring for 40-60min at a rotation speed of 80-120rpm, and sending the mixed material into an extruder for extrusion, and the tablet thickness is 1-2mm; S3, crushing, grinding and sieving the cooled pressed tablets to finally obtain a powder coating of 100-120 mesh.

[0016] As a further technical solution, the temperature of the extruder feeding section is 60-70°C, the temperature of the melting section is 95-105°C, and the temperature of the discharging section is 90-100°C.

[0017] The working principle and beneficial effects of the present invention are: The present invention utilizes the compounding effect of modified alumina and nano calcium silicate to significantly improve the corrosion resistance and flame retardancy of the coating, and maintain certain performance under extreme environments. The improvement of these properties is mainly due to the synergistic effect of modified nano alumina and nano calcium silicate, and the good compatibility between them and the resin matrix under the action of the silane coupling agent.

[0018] Among them, a layer of zinc oxide is coated on the surface of nano-alumina. Zinc oxide itself has high chemical stability and is not easy to react with common corrosive substances. It can form a dense protective layer. This protective layer can effectively block the direct contact between corrosive media (such as moisture, acid, alkali, etc.) and nano-alumina, thereby slowing down or preventing the corrosion reaction.

[0019] In addition, zinc oxide can form a protective layer during the combustion process to isolate oxygen and heat. Nano-alumina itself also has certain flame retardant properties. Its high melting point and high thermal stability can slow down the burning speed of the coating. When zinc oxide is coated on the surface of nano-alumina, the two can play a synergistic role and jointly improve the flame retardant properties of powder coatings.

[0020] In extreme environments, the zinc oxide coating on the surface of nano-alumina can maintain its structural integrity and continue to play a protective role. Zinc oxide has a high melting point and is not easy to melt or decompose at high temperatures, so it can maintain its flame retardant and corrosion resistance at extreme temperatures. At the same time, the zinc oxide coating can also prevent the nano-alumina from undergoing structural changes due to erosion by environmental factors, thereby maintaining its original performance. Under low temperature conditions, the stability of the zinc oxide coating is usually enhanced because low temperature slows down the destruction rate of the passivation film. Therefore, the protective effect of the passivation film in low temperature environments is more significant.

[0021] The nano calcium silicate in the present invention has good chemical stability, can keep its structure unchanged in a variety of corrosive media, thereby effectively blocking the penetration of corrosive media, and its performance is better than that of calcium carbonate, and has a higher melting point and heat resistance, can keep its structure stable in a high temperature environment, and is not easy to burn or decompose, thereby effectively improving the flame retardancy of the coating. The melting point of nano calcium carbonate is relatively low, and it may be more likely to decompose or burn in a high temperature environment, resulting in a decrease in flame retardancy.

[0022] The modified nano-alumina and nano-calcium silicate are selected for compounding in the present invention, which can exert a synergistic flame retardant effect and further improve the flame retardant performance of the coating. The compounding of the coated modified nano-alumina and nano-calcium silicate can improve the dispersibility of each other, so that they are more evenly dispersed in the resin matrix, which helps to form a denser coating structure and improve the overall performance of the coating. It can also enable the coating to maintain certain performance in extreme environments to a certain extent, and the interaction between the two can reduce the impact of environmental factors on the coating and extend the service life of the coating.

[0023] In the present invention, ammonia water is selected as an alkaline solution to react with zinc ions to generate zinc hydroxide precipitates. During the preparation process, due to the weak alkalinity of ammonia water and its special reaction properties with zinc ions, more complex zinc ammonia complexes may be formed, and these complexes may be converted into aluminum oxide with special surface properties in the subsequent treatment process. Sodium hydroxide, as a strong base, reacts rapidly with zinc ions to generate zinc hydroxide precipitates. The reaction process is relatively simple, and the properties of the generated zinc hydroxide precipitates are relatively simple. The subsequent modification effect may be limited by its initial chemical composition and structure. Due to the weak alkalinity of ammonia water and its complexation with zinc ions, the surface of the generated aluminum oxide may have more active groups (such as hydroxyl groups, etc.), which are conducive to forming chemical bonds with other components in the coating, thereby improving the overall performance of the coating. In addition, the complexation also forms special microstructures on the surface of the aluminum oxide particles, which are conducive to enhancing the corrosion resistance and flame retardancy of the coating. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be noted that the molecular weight of the epoxy resin in the present invention is 400-500, the epoxy equivalent is 210-240g / eq, and the epoxy resin E44 is selected as the raw material in the following examples and comparative examples; the viscosity of the polyimide resin at 50°C in the present invention is 30000-60000 mPa·s, and the resin solid content is 80 wt%-85wt%; the polyimide resin KH-320N is selected as the raw material in the following examples and comparative examples.

[0026] Example 1 The present embodiment provides a corrosion-resistant flame-retardant powder coating, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 11 parts of modified nano-alumina, 7 parts of nano-calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 2000mL of deionized water, performing ultrasonic dispersion for 35min at a power of 110W, then adding 1.5g of ZnCl2·6H2O, continuing ultrasonication, stirring at a speed of 130r / min to obtain a mixed solution, adding ammonia water with a concentration of 1mol / L under stirring while maintaining the speed, and the dropping speed of the ammonia water is 10mL / min until the pH is 10, continuing stirring for 50min, then adding deionized water until the pH is 7, filtering, and drying at 70°C to obtain the product; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the model of leveling agent is BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0027] Example 2 The present embodiment provides a corrosion-resistant flame-retardant powder coating, which is composed of the following raw materials in parts by weight: 45 parts of epoxy resin, 15 parts of polyimide resin, 10 parts of modified nano-alumina, 6 parts of nano-calcium silicate, 2 parts of graphene nanosheets, 8 parts of expanded graphite, 18 parts of polyamide curing agent, 2 parts of silane coupling agent, 1 part of leveling agent, 0.5 parts of dispersant, 0.5 parts of antioxidant and 0.5 parts of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 1900mL of deionized water, performing ultrasonic dispersion for 40min at a power of 100W, then adding 1.3g of ZnCl2·6H2O, continuing ultrasonication, stirring at a speed of 125r / min to obtain a mixed solution, adding ammonia water with a concentration of 1mol / L under stirring while maintaining the speed, and the dropping speed of the ammonia water is 10mL / min until the pH is 10, continuing stirring for 40min, then adding deionized water until the pH is 7, filtering, and drying at 60°C to obtain the product; Among them, the model of silane coupling agent is KH560; the model of polyamide curing agent is 651; the model of imidazole accelerator is 1B2PZ; the model of leveling agent is BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 55°C for 120 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 160 rpm and stir for 30 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 20 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 60 minutes at a speed of 80 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 100-mesh powder coating.

[0028] Example 3 The present embodiment provides a corrosion-resistant flame-retardant powder coating, which is composed of the following raw materials in parts by weight: 55 parts of epoxy resin, 25 parts of polyimide resin, 12 parts of modified nano-alumina, 8 parts of nano-calcium silicate, 3 parts of graphene nanosheets, 10 parts of expanded graphite, 22 parts of polyamide curing agent, 4 parts of silane coupling agent, 1.4 parts of leveling agent, 1.5 parts of dispersant, 0.7 parts of antioxidant and 1.5 parts of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 2100mL of deionized water, performing ultrasonic dispersion for 30min at a power of 120W, then adding 1.6g of ZnCl2·6H2O, continuing ultrasonication, stirring at a speed of 140r / min to obtain a mixed solution, adding ammonia water with a concentration of 1mol / L under stirring while maintaining the speed, and the dropping speed of the ammonia water is 10mL / min until the pH is 10, continuing stirring for 60min, then adding deionized water until the pH is 7, filtering, and drying at 80°C to obtain the product; Among them, the model of silane coupling agent is KH570; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the model of leveling agent is BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 65°C for 100 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 160 rpm and stir for 30 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 20 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 40 minutes at a speed of 120 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 120-mesh powder coating.

[0029] Example 4 The present embodiment provides a corrosion-resistant flame-retardant powder coating, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 12 parts of modified nano-alumina, 8 parts of nano-calcium silicate, 2 parts of graphene nanosheets, 8 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 2000mL of deionized water, performing ultrasonic dispersion for 35min at a power of 10W, then adding 1.5g of ZnCl2·6H2O, continuing ultrasonication, stirring at a speed of 125r / min to obtain a mixed solution, adding ammonia water with a concentration of 1mol / L while maintaining the speed and stirring, and the ammonia water is added at a dripping speed of 10mL / min until the pH is 10, continuing stirring for 60min, then adding deionized water until the pH is 7, filtering, and drying at 60°C to obtain the product; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 651; the model of imidazole accelerator is 1B2PZ; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 65°C for 100 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 200 rpm and stir for 20 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 20 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 60 minutes at a speed of 120 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0030] Comparative Example 1 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 11 parts of modified nano-alumina, 7 parts of nano-calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 2000mL of deionized water and performing ultrasonic dispersion for 35min at a power of 110W, then adding 1.09g of zinc acetate, continuing ultrasonication, and stirring at a speed of 130r / min to obtain a mixed solution, adding a 1mol / L sodium hydroxide aqueous solution under stirring conditions while maintaining the speed, and adding at a drop rate of 10mL / min until the pH is 10, continuing stirring for 50min, and then adding deionized water until the pH is 7, filtering, and drying at 70°C to obtain the obtained solution; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0031] Comparative Example 2 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 4 parts of nano-alumina, 7 parts of zinc oxide, 7 parts of nano-calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of zinc oxide comprises: adding 1.5g ZnCl2·6H2O to 2000mL deionized water, performing ultrasonic dispersion for 35min at a power of 110W, stirring at a speed of 130r / min to obtain a mixed solution, maintaining the speed and continuing to add ammonia water with a concentration of 1mol / L under stirring conditions, the ammonia water dropping speed is 10mL / min, until the pH is 10, continuing to stir for 50min, then adding deionized water until the pH is 7, filtering, and drying at 70°C to obtain the obtained solution; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying nano-alumina, zinc oxide, nano-calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0032] Comparative Example 3 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 11 parts of nano-alumina, 7 parts of nano-calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0033] Comparative Example 4 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 11 parts of zinc oxide, 7 parts of nano calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of zinc oxide comprises: adding 1.5g ZnCl2·6H2O to 2000mL deionized water, performing ultrasonic dispersion for 35min at a power of 110W, stirring at a speed of 130r / min to obtain a mixed solution, maintaining the speed and continuing to add ammonia water with a concentration of 1mol / L under stirring conditions, the ammonia water dropping speed is 10mL / min, until the pH is 10, continuing to stir for 50min, then adding deionized water until the pH is 7, filtering, and drying at 70°C to obtain the obtained solution; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying zinc oxide, nano-calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0034] Comparative Example 5 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 7 parts of nano calcium silicate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying nano calcium silicate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0035] Comparative Example 6 In this comparative example, a corrosion-resistant flame-retardant powder coating is provided, which is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of polyimide resin, 11 parts of modified nano-alumina, 7 parts of nano-calcium carbonate, 2.5 parts of graphene nanosheets, 9 parts of expanded graphite, 20 parts of polyamide curing agent, 3 parts of silane coupling agent, 1.2 parts of leveling agent, 1 part of dispersant, 0.6 parts of antioxidant and 1 part of imidazole accelerator; The preparation method of modified nano-alumina comprises: adding 0.5g of nano-alumina to 2000mL of deionized water, performing ultrasonic dispersion for 35min at a power of 110W, then adding 1.5g of ZnCl2·6H2O, continuing ultrasonication, stirring at a speed of 130r / min to obtain a mixed solution, adding ammonia water with a concentration of 1mol / L under stirring while maintaining the speed, and the dropping speed of the ammonia water is 10mL / min until the pH is 10, continuing stirring for 50min, then adding deionized water until the pH is 7, filtering, and drying at 70°C to obtain the product; Among them, the model of silane coupling agent is KH550; the model of polyamide curing agent is 650; the model of imidazole accelerator is 2MZ-A; the leveling agent is leveling agent BYK-310; the dispersant is dispersant 5040; the antioxidant is antioxidant 168; The preparation method of the corrosion-resistant flame-retardant powder coating comprises the following steps: S1: drying the modified nano-alumina, nano-calcium carbonate, graphene nanosheets and expanded graphite at 60°C for 110 min; S2: Mix the epoxy resin and the polyimide resin with the powder dried in step S1, keep the speed at 180 rpm and stir for 25 minutes, then add the silane coupling agent, leveling agent, dispersant and antioxidant to the mixed system in order and continue to stir for 25 minutes, finally add the polyamide curing agent and imidazole accelerator, continue to stir for 50 minutes at a speed of 100 rpm, and send the mixed materials into a melt extruder for melt extrusion, and the thickness of the sheet is 2 mm; the temperature of the feeding section of the extruder is 65° C., the temperature of the melting section is 100° C., and the temperature of the discharging section is 95° C.; S3 crushes, grinds and sieves the cooled pressed tablets to finally obtain a 110-mesh powder coating.

[0036] Test example: The powder coatings prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-6 were sprayed on 50 mm × 100 mm aluminum sheets by high-voltage electrostatic spraying, with a coating thickness of 90 μm, a curing temperature of 200° C., and a curing time of 30 min to obtain test samples, and the performance was explored. The prepared powder coatings were tested as follows: 1. Flame retardant grade: Tested in accordance with UL94; 2. Salt spray resistance test: refer to GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes. The concentration of sodium chloride solution is 55g / L, the test period is 1000h, and the temperature is controlled at -30℃ and 50℃ for parallel testing to observe whether the paint film of the sample has blistering or peeling.

[0037] 3. Adhesion test: refer to GB / T9286-2021 "Scratch test for paint and varnish films". The smaller the number, the better the adhesion.

[0038] The test results are shown in Table 1 below: Table 1

[0039] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A corrosion-resistant flame-retardant powder coating, characterized in that: The invention is composed of the following raw materials in parts by weight: 45-55 parts of epoxy resin, 15-25 parts of polyimide resin, 10-12 parts of modified nano-alumina, 6-8 parts of nano-calcium silicate, 2-3 parts of graphene nanosheets, 8-10 parts of expanded graphite, 18-22 parts of polyamide curing agent, 2-4 parts of silane coupling agent, 1-1.4 parts of leveling agent, 0.5-1.5 parts of dispersant, 0.5-0.7 parts of antioxidant and 0.5-1.5 parts of imidazole accelerator.

2. The corrosion-resistant flame-retardant powder coating according to claim 1, characterized in that: The epoxy resin has a molecular weight of 400-500 and an epoxy equivalent of 210-240 g / eq; the polyimide resin has a viscosity of 30000-60000 mPa·s at 50° C. and a resin solid content of 80 wt%-85 wt%.

3. The corrosion-resistant flame-retardant powder coating according to claim 1, characterized in that: The preparation method of the modified nano-alumina comprises: adding nano-alumina to deionized water for ultrasonic dispersion, then adding ZnCl2·6H2O, continuing ultrasonic dispersion to obtain a mixed solution, adding ammonia water with a concentration of 1 mol / L under stirring conditions until the pH value is 10, continuing stirring, then adding deionized water until the pH value is 7, filtering, and drying to obtain the modified nano-alumina.

4. The corrosion-resistant flame-retardant powder coating according to claim 3, characterized in that: The weight ratio of the nano-alumina to ZnCl2·6H2O is 1:3-5.

5. The corrosion-resistant flame-retardant powder coating according to claim 3, characterized in that: The power of the ultrasonic dispersion is 100-120W; the rotation speed of the stirring is 120-140r / min.

6. The corrosion-resistant flame-retardant powder coating according to claim 3, characterized in that: The dropping speed of the ammonia water is 9-11 mL / min.

7. The corrosion-resistant flame-retardant powder coating according to claim 1, characterized in that: The model of the silane coupling agent is any one of KH550, KH560 and KH570; the polyamide curing agent includes polyamide curing agent 650 or polyamide curing agent 651; and the imidazole accelerator includes imidazole accelerator 2MZ-A or imidazole accelerator 1B2PZ.

8. The corrosion-resistant flame-retardant powder coating according to claim 1, characterized in that: The model of the leveling agent is BYK-310; the dispersant is dispersant 5040; and the antioxidant is antioxidant 168.

9. The method for preparing a corrosion-resistant flame-retardant powder coating according to any one of claims 1 to 8, characterized in that the steps include: S1. Drying the modified nano-alumina, nano-calcium silicate, graphene nanosheets and expanded graphite at a temperature of 55-65° C. for 100-120 min; S2, mixing the epoxy resin and the polyimide resin with the powder dried in step S1, maintaining the rotation speed at 160-200rpm and stirring for 20-30min, then sequentially adding silane coupling agent, leveling agent, dispersant and antioxidant and continuing stirring for 20-30min, finally adding polyamide curing agent and imidazole accelerator, continuing stirring for 40-60min at a rotation speed of 80-120rpm, and sending the mixed material into an extruder for extrusion, and the tablet thickness is 1-2mm; S3, crushing, grinding and sieving the cooled pressed tablets to finally obtain a powder coating of 100-120 mesh.

10. The method for preparing a corrosion-resistant flame-retardant powder coating according to claim 9, characterized in that: The temperature of the feeding section of the extruder is 60-70°C, the temperature of the melting section is 95-105°C, and the temperature of the discharging section is 90-100°C.

Citation Information

Cited By

  • Nano ceramic ultrahigh-hardness powder coating and preparation method thereof

    CN121379351A

  • A nano-ceramic ultra-high hardness powder coating and a preparation method thereof

    CN121379351B